THE EFFECTIVENESS OF LEGAL PROTECTION FOR DEBTORS IN COLLATERAL EXECUTION: AN EMPIRICAL STUDY OF CREDIT AGREEMENTS AT KREDITPLUS FINANCE MADIUN BRANCH - Inggit Septiyanto Noer Oemahati; Anik Tri Haryani; Krista Yitawati (Yayasan Adra Karima Hubbi, 2026)
This study aims to comprehensively analyze the forms of legal protection for debtors regarding the imposition of late payment penalties in non-performing vehicle financing cases at the Madiun Branch of Kreditplus Finance. Using empirical legal research with a descriptive qualitative approach, the study reveals that legal protection is realized through preventive mechanisms, such as contract clause transparency, due date notifications, and credit restructuring, as well as repressive mechanisms via internal complaints, Financial Services Authority (OJK) mediation, and litigation. However, the implementation of this protection faces significant obstacles in the field. These obstacles include low debtor legal awareness, the dominance of unbalanced standard contracts, vulnerable economic conditions of the community, and technical banking operational constraints. In conclusion, although consumer protection regulations are available, the debtor's bargaining position in practice remains weak due to information asymmetry. Therefore, simplifying contract information and enhancing substantive oversight by the OJK are necessary to achieve justice and a sustainable balance of rights and obligations between creditors and debtors in the financial services sector.